2000
DOI: 10.1046/j.1460-2695.2000.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact fatigue of automotive gears: evolution and effects of residual stresses introduced by surface treatments

Abstract: Helical gears from an automotive gearbox, previously subjected to the surface treatments of carbo‐nitriding and shot‐peening, were submitted to contact fatigue tests. The X‐ray diffraction technique was used to characterize the evolution of different mechanical and metallurgical parameters as a function of gear damage. Particular attention was paid to residual stress relief. A numerical model was developed to predict residual stress relaxation and estimate the most likely localization of contact fatigue crack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 4 publications
(6 reference statements)
3
21
0
Order By: Relevance
“…However, the hybrid process cannot be always advantageous to the application of steels. For instance, it is shown in [11] that when both carbonitrided gear and carbonitrided plus peened gear made of AISI 4130 steel are subjected to contact fatigue testing, fatigue damages, which are ought to be in different modes, are found to occur after about the same testing time for both types of methods. is could most probably be a consequence of the use of inappropriate shot peening condition; the extreme shot bombardment on the surface can cause roughness increment and flaw occurrence and therefore outweigh the beneficial effect brought by the hybrid process.…”
Section: Introductionmentioning
confidence: 99%
“…However, the hybrid process cannot be always advantageous to the application of steels. For instance, it is shown in [11] that when both carbonitrided gear and carbonitrided plus peened gear made of AISI 4130 steel are subjected to contact fatigue testing, fatigue damages, which are ought to be in different modes, are found to occur after about the same testing time for both types of methods. is could most probably be a consequence of the use of inappropriate shot peening condition; the extreme shot bombardment on the surface can cause roughness increment and flaw occurrence and therefore outweigh the beneficial effect brought by the hybrid process.…”
Section: Introductionmentioning
confidence: 99%
“…This typical configuration or damage morphology has also been described in the literature as a triangular, v-shaped, sea-shell shaped or fan-shaped crack. Multiple studies have investigated or reported the typical v-shaped surface damage for both bearing and gear applications [4,5,2,[6][7][8][9][10]. The angle at the apex of the spall or crater, a in Fig.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…Batista et al [12] developed the numerical model to analyze fatigue failure, taking into account the effect of surface characteristics including the roughness. Norimune et al [13] experimentally investigated the effect of roughness on the contact fatigue life using the Four-roller type rolling contact machine.…”
Section: Introductionmentioning
confidence: 99%